ANALISIS REPRESENTASI PRIBUMI DAN KETIDAKSETARAAN GENDER PEREMPUAN DALAM FILM BUMI MANUSIA - Achmad Yuhdi; Octavianty, Widya (FKIP, Universitas Palangka Raya, 2023)
This study aims to describe the representation of indigenous women and gender inequality in the film Bumi Manusia and aims to add to being a reference for students in identifying, describing, analyzing, and motivating in studying film analysis in the form of review text to achieve the learning objectives listed in the 2013 curriculum. The method used is a qualitative inductive method for the purpose of building understanding in meaning. The qualitative approach is primarily aimed at exploring, describing, and explaining. Based on the collected data, eight indigenous representations and gender inequality of women were found in the film Bumi Manusia. The results of this study also show that the representation of indigenous women and gender inequality contained in the short story is still quite relevant to today's life.